Research on drop-weight impact of continuous carbon fiber reinforced 3D printed honeycomb structure. (December 2021) - Dou, Hao; Ye, Wenguang; Zhang, Dinghua; Cheng, Yunyong; Huang, Kuidong; Yang, Fuqiang; Rudykh, Stephan
Abstract: Continuous carbon fiber reinforced 3D printed parts have been widely researched due to their excellent mechanical and thermal properties. This research presents a continuous carbon fiber reinforced 3D printed honeycomb structure, which is manufactured by a modified 3D printer. For comparison, the drop-weight impact test of the honeycomb structure with continuous fiber reinforced and non-reinforced pure matrix of polylactide (PLA) is printed and the results show that the continuous carbon fiber greatly improved the impact resistance of the honeycomb structure. The finite element model is established to simulate the impact process, which is in good agreement with the experimental results. Cone beam computed tomography (CT) is also used to detect the internal damage of honeycomb structure during impact, it is found from the detection images that the main failure modes of the structure are the failure of matrix-fiber interface and the destruction between adjacent printing paths. Graphical Abstract: ga1